2011
DOI: 10.1371/journal.pone.0029491
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Biological Functions of Compounds Based on Chemical-Chemical Interactions

Abstract: Given a compound, how can we effectively predict its biological function? It is a fundamentally important problem because the information thus obtained may benefit the understanding of many basic biological processes and provide useful clues for drug design. In this study, based on the information of chemical-chemical interactions, a novel method was developed that can be used to identify which of the following eleven metabolic pathway classes a query compound may be involved with: (1) Carbohydrate Metabolism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 55 publications
2
78
0
Order By: Relevance
“…Likewise, it has been indicated by some pioneer studies [13, 16] that interactive compounds follow the similar rules. Since side effect is one part of biological functions of drugs, using the properties of interactive compounds to identify drugs side effects is a feasible scheme.…”
Section: Methodsmentioning
confidence: 74%
See 3 more Smart Citations
“…Likewise, it has been indicated by some pioneer studies [13, 16] that interactive compounds follow the similar rules. Since side effect is one part of biological functions of drugs, using the properties of interactive compounds to identify drugs side effects is a feasible scheme.…”
Section: Methodsmentioning
confidence: 74%
“…Thus, the prediction of drugs side effects is a multilabel classification problem. Like the case in dealing with compounds with multiple properties [13, 16], the proposed method would provide the order information of side effects from the most likely to the least likely.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have indicated that computational approaches can timely provide very useful insights for both basic research and drug development, such as predicting drug−target interaction networks , predicting HIV cleavage sites in proteins (Chou, 1996), prediction of body fluids (Hu et al, 2011a), predicting protein metabolic stability (Huang et al 2010), predicting signal peptides (Chou and Shen, 2007), predicting the network of substrate−enzyme−product triads (Chen et al, 2010), predicting protein subcellular locations (Chou et al, 2011), predicting biological functions of compounds based on chemicalchemical interactions (Hu et al, 2011b). Actually, several novel mathematical approaches and physical concepts have been introduced into molecular biology, such as Mahalanobis distance (Chou, 1995), pseudo amino acid composition (Chou, 2001), graph and diagram analysis (Zhou and Deng, 1984;Andraos, 2008;Chou, 2010), cellular automaton (Xiao et al, 2009), grey theory (Xiao et al, 2008), low-frequency (or Terahertz frequency) phonons (Chou, 1989), which can significantly stimulate the development of biological and medical science.…”
Section: Introductionmentioning
confidence: 99%